2005
DOI: 10.1562/2004-10-12-ra-341.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on the Fluorescence Anisotropy Decay Dynamics of Coumarin-153 Dye in Triton-X-100 and Brij-35 Micellar Solutions¶

Abstract: The fluorescence anisotropy decay dynamics of the fluorescent probe Coumarin-153 (C153) have been investigated in two neutral micelles, Triton-X-100 (TX-100) and Brij-35 (BJ-35), at different temperatures and analyzed on the basis of the well-known two-step model. Because steady-state fluorescence spectra of the above probe do not show any noticeable changes with respect to temperature, for either of the studied micelles, suggests a similar polarity in the microenvironment around the probe at all the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…[50] Higher temperature leads to as horter rotational correlation time, and therefore, lower anisotropy according to the Perrin equation. Fluorescenceanisotropyh as ac omplex dependence on temperature.…”
Section: Fluorescence Anisotropy(fa)n Anothermometrymentioning
confidence: 99%
“…[50] Higher temperature leads to as horter rotational correlation time, and therefore, lower anisotropy according to the Perrin equation. Fluorescenceanisotropyh as ac omplex dependence on temperature.…”
Section: Fluorescence Anisotropy(fa)n Anothermometrymentioning
confidence: 99%
“…The appreciable difference of average lifetime of 6MQ + in the SDS micelles than that in pure water rules out the possibility of location of 6MQ + molecules around the bulk phase and suggests that most of the 6MQ + molecules in SDS micelles are localized in micelle-water interface. The single exponential nature of the fluorescence decay in micellar systems indicate that the probe molecules are mostly solubilized at similar sites of the micelles [51][52][53]. 6MQ + giving multi-exponential decay at different concentrations of micellar solution at different emission wavelengths suggest that the probe molecule is not located in a single type of site of the micelles.…”
Section: Fluorescence Lifetimesmentioning
confidence: 99%
“…This phenomenon is attributed to a disruption of hydrogen bonding, between the water and the polyethoxylate units in the molecule. Although studies on the temperature dependence of NP micelle size have yet to be reported, previous studies on other surfactants such as Triton X-100, Brij-35, and pyridinium surfactants also indicate a temperature dependence [16,44,[47][48][49][50]. While temperature does in fact affect micelle size, it was not included as a parameter in the determination of the model.…”
Section: Temperaturementioning
confidence: 99%